2011
DOI: 10.1016/j.molcel.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Regulatory Mapping Indicates that the RNA-Binding Protein HuR Couples Pre-mRNA Processing and mRNA Stability

Abstract: SUMMARY RNA-binding proteins coordinate the fates of multiple RNAs, but the principles underlying these global interactions remain poorly understood. We elucidated regulatory mechanisms of the RNA-binding protein HuR, by integrating data from diverse high-throughput targeting technologies, specifically PAR-CLIP, RIP-chip, and whole-transcript expression profiling. The number of binding sites per transcript, degree of HuR-association, and degree of HuR-dependent RNA stabilization were positively correlated. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
710
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 601 publications
(775 citation statements)
references
References 51 publications
52
710
4
1
Order By: Relevance
“…The agreement between the methods is significant (p < 1.91 £ 10 ¡10 , Fisher's exact test), and higher than observed in previous comparisons. 27 RIP-Seq targets that were absent in the iCLIP data tend to be transcripts with low expression levels (data not shown), confirming our expectation that RIP-Seq is the more abundance-sensitive method with higher coverage than iCLIP. Besides interactions with mRNAs and pre-mRNAs, we identified 2 miRNAs as putative hnRNP H1 targets (miR-612 and miR-3652), and 12 long non-coding RNAs (NEAT1, SNHG3, MALAT1, FTX, SNHG4, TUG1, HOTAIRM1, GNAS-AS1, MIR22HG, BDNF-AS, OIP5-AS1, MIR17HG).…”
Section: Identification Of Target Transcripts and Binding Sitessupporting
confidence: 77%
“…The agreement between the methods is significant (p < 1.91 £ 10 ¡10 , Fisher's exact test), and higher than observed in previous comparisons. 27 RIP-Seq targets that were absent in the iCLIP data tend to be transcripts with low expression levels (data not shown), confirming our expectation that RIP-Seq is the more abundance-sensitive method with higher coverage than iCLIP. Besides interactions with mRNAs and pre-mRNAs, we identified 2 miRNAs as putative hnRNP H1 targets (miR-612 and miR-3652), and 12 long non-coding RNAs (NEAT1, SNHG3, MALAT1, FTX, SNHG4, TUG1, HOTAIRM1, GNAS-AS1, MIR22HG, BDNF-AS, OIP5-AS1, MIR17HG).…”
Section: Identification Of Target Transcripts and Binding Sitessupporting
confidence: 77%
“…The regulation of cytokines by miR-9 is HuR-dependent HuR is a known regulator of inflammation by mediating the stability and the translation of mRNAs holding ARE motifs, 16 moreover, all the cytokines in this study deregulated by miR-9 contain several repeats of the HuR-binding motif identified recently by PAR-CLIP 25,26 (Supplementary 3B). Because we found HuR to be a direct target of miR-9, we next analysed the role of HuR in the regulation of cytokines by miR-9.…”
Section: Introductionmentioning
confidence: 60%
“…Our results show that methylated RNAs tend to be more abundant than nonmethylated RNAs (Figure 3a–e) in old vs. young. In addition, CDF analysis of AUF1 and HuR target mRNAs (Mukherjee et al., 2011; Yoon et al., 2014) from MeRIP‐seq and total RNA‐seq data has shown that AUF1 and HuR target RNAs are downregulated further than nontarget mRNAs once they are methylated (Figure 3f,g, Figures S2 and S3). These results imply possible involvement of AUF1 and HuR in the stability regulation of m6A‐modified RNA (Visvanathan et al., 2017).…”
Section: Resultsmentioning
confidence: 99%